2021
DOI: 10.5194/aab-64-211-2021
|View full text |Cite
|
Sign up to set email alerts
|

The expression and mutation of <i>BMPR1B</i> and its association with litter size in small-tail Han sheep (<i>Ovis aries</i>)

Abstract: Abstract. Previous studies have shown that BMPR1B promotes follicular development and ovarian granulosa cell proliferation, thereby affecting ovulation in mammals. In this study, the expression and polymorphism of the BMPR1B gene associated with litter size in small-tail Han (STH) sheep were determined. The expression of BMPR1B was detected in 14 tissues of STH sheep during the follicular phase as well as in the hypothalamic–pituitary–gonadal (HPG) axis of monotocous and polytocous STH sheep during the follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In addition, the FecB mutation was absent in Thoka, Woodlands, Olkuska, Lacaune, Belclare, and Cambridge sheep breeds [32] This FecB mutation effects not only on litter size trait but also reported to have effects on other traits related with reproductive efficiency of ewes such as fertility and embryo survival, lamb survival, lamb growth, carcass quality, wool production that supports the present findings [35]. Moreover, the g.29380965A>G locus of BMPR1B gene found to had negative effect on the litter size of STH sheep of China, but combination with FecB genotype produce significantly (P<0.05) higher litter size [36].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the FecB mutation was absent in Thoka, Woodlands, Olkuska, Lacaune, Belclare, and Cambridge sheep breeds [32] This FecB mutation effects not only on litter size trait but also reported to have effects on other traits related with reproductive efficiency of ewes such as fertility and embryo survival, lamb survival, lamb growth, carcass quality, wool production that supports the present findings [35]. Moreover, the g.29380965A>G locus of BMPR1B gene found to had negative effect on the litter size of STH sheep of China, but combination with FecB genotype produce significantly (P<0.05) higher litter size [36].…”
Section: Discussionsupporting
confidence: 85%
“…For example, many studies have shown that BMPR1B is associated with litter size in animals [32][33][34]. It is the main gene that affects the ovulation rate and litter size in sheep [35][36][37]. In addition, a series of studies have confirmed that the BMPR1B can affect follicular development, ovulation [38], and cause ovarian insufficiency [39].…”
Section: Discussionmentioning
confidence: 99%
“…BMPR1B defects in mice have been shown to cause infertility [ 58 ], and high expression of BMPR1B in ovaries has been related to highly prolific sheep and goats [ 20 , 59 ]. In this study, the SINE-insertion individuals exhibited higher expression of BMPR1B in ovary and greater first litter size in comparison to individuals without SINE insertion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression difference was not found in back fat and muscle among these genotypes. It is possible that the expression of BMPR1B in the tissues of brain was relatively high compared with other tissues, including the ovary [ 20 , 23 ], which made it play a major role through modulating the hypothalamic–pituitary axis to affect the growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation